Fault Tolerance Controls of a Three-leg Two-phase Inverter to Secure Functional Reliability for Heated Windshield in xEV 전기차 발열 유리의 기능 신뢰성 확보를 위한 3레그 2상 인버터의 허용제어 - Jeong, Gi Heon; Lee, Hyung Woo; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2023)
This paper proposes a fault tolerance control method for a three-leg two-phase inverter to secure the functional reliability of xEV components. It diagnoses an open-switch fault with the size of the current sensed within 2 cycles in real time without applying conventional coordinate conversion and complex formulas. The MOSFET that has failed stops operating, and another MOSFET in the same leg are set to always conduct. In the three-leg two-phase inverter, the fault state is classified for each case in which an open-switch fault diagnosis has occurred, and the duty ratio of the A, B, and C phases is adjusted. Through duty ratio adjustment and phase shift control for each switch of the inverter, functional reliability is secured by supplying the same power as before the failure. The functional reliability of an inverter is verified through simulations and experimental result.
Keywords: Fault control; Fault tolerance control; Funtional reliability; Inverte reliability; MOSFETs; Open faults; Phase inverter; Switch open fault; Two phase; XEV inverte; Fault control; Fault tolerance; Funtional reliability; Inverter reliability; Switch open fault; xEV Inverter